No association between polymorphisms/haplotypes of the vascular endothelial growth factor gene and preeclampsia - Garza Veloz, Idalia; Castruita De la Rosa, Claudia; Cortes Flores, Raúl; Martínez Gaytán, Victoria; Rivera Muñoz, José E.; García Mayorga, Elda A.; Meza Lamas, Esteban; Rojas Martínez, Augusto; Ortiz López, Rocío; Martínez Fierro, Margarita de la Luz (2011)
Background: Preeclampsia (PE) is the first worldwide cause of death in pregnant women, intra-uterine growth retardation, and fetal prematurity. Some vascular endothelial grown factor gene (VEGF) polymorphisms have been associated to PE and other pregnancy disturbances. We evaluated the associations between VEGF genotypes/ haplotypes and PE in Mexican women. Methods: 164 pregnant women were enrolled in a case-control study (78 cases and 86 normotensive pregnant controls). The rs699947 (-2578C/A), rs1570360 (-1154G/A), rs2010963 (+405G/C), and rs25648 (-7C/T), VEGF variants were discriminated using Polymerase Chain Reaction - Restriction Fragment Length Polymorphism (PCR-RFLP) methods or Taqman single nucleotide polymorphism (SNP) assays. Results: The proportions of the minor allele for rs699947, rs1570360, rs2010963, and rs25648 VEGF SNPs were 0.33, 0.2, 0.39, and 0.17 in controls, and 0.39, 0.23, 0.41, and 0.15 in cases, respectively (P values > 0.05). The most frequent haplotypes of rs699947, rs1570360, rs2010963, and rs25648 VEGF SNPs, were C-G-C-C and C-G-G-C with frequencies of 0.39, 0.21 in cases and 0.37, 0.25 in controls, respectively (P values > 0.05) Conclusion: There was no evidence of an association between VEGF alleles, genotypes, or haplotypes frequencies and PE in our study